Political Economy of Industrial Policy Making Indonesia 4.0: a Strategy for Strengthening the National Manufacturing Industry in Global Value Chains (GCV) - Miftahudin, Erwin; Sudiarto, Tatok Djoko (PT FORMOSA CENDEKIA GLOBAL, 2025)
This paper discusses the Making Indonesia 4.0 policy that aims to strengthen Indonesia's manufacturing sector and improve global competitiveness through Industry 4.0 technology. This research identifies challenges and opportunities for Indonesia in implementing the policy, with a focus on strengthening Indonesia's position in Global Value Chains (GVCs). Through the adoption of advanced technologies such as robotics, artificial intelligence (AI), and the Internet of Things(IoT), Indonesia's manufacturing sector is Expected to increase its efficiency, reduce dependence on imports, and improve product quality. However, the main challenges faced are the limited readiness of human resources and digital infrastructure. In addition, the policy also emphasizes the importance of strengthening an integrated industrial ecosystem and increasing foreign investment to support more sustainable industrial development.